Genre-Based Approach for Better Recount Writing in the Classroom (Universitas PGRI Sumatera Barat, 2023)
The purpose of this study is to see if there are any variations in students' writing abilities before and after using a genre-based approach, and how to improve students' writing skills in studying recount text using a genre-based approach. This study is a single-subject experimental study. The data collection instrument was a test of students' writing abilities in the form of recount text. The sample size in this study was 15 participants, from class X TKJ 3. The paired t-test and the N-gain technique were used to analyze data from students' writing assignments. Based on data analysis utilizing the paired sample t-test, it was determined that students' writing talents differed before and after applying the genre-based approach. The N-Gain test findings indicate that students' writing abilities improved significantly after adopting a genre-based approach to recount text content.